Efektivitas Pembelajaran Secara Daring dengan Menggunakan Aplikasi Whatapp terhadap Hasil Belajar - Arief Budi Pratomo; Ali Ramatni; Dian Ratna Sari; Joni Wilson Sitopu; Moh Solehuddin; Ms Viktor Purhanudin (Departement of Mathematics Education, 2023)
process is very different from the offline or face-to-face learning process, such as the way of delivering material and how to assess it. It is also of course that there are many obstacles experienced by educators and students during the online learning process. This study aims to see whether online learning using the Whatsapp application on learning outcomes is effective or not. Based on the results of research and hypothesis testing that has been discussed, it can be concluded that the data analysis used is a hypothesis test, where the hypothesis test is used to see the effectiveness of online learning using the Whatsapp application on learning outcomes. In this study hypothesis testing used a one-sample t-test. Based on the results of the study, a p-value or sig value was obtained. = 0.000 < α = 0.05 So it can be said H_1 accepted, it can be concluded that online learning using the Whatsapp application on learning outcomes is effective.